Beyond the usual suspects: using cross-sectoral partnerships to target and engage new citizen scientists - Iwanycki Ahlstrand, Natalie; Tøttrup, Anders P. (Frontiers in Environmental Science, 2023)
Citizen science offers enormous benefits to enhance public knowledge and understanding of science. Several opportunities to engage and share information with citizens are possible in citizen science projects. Recent evidence demonstrates however that individuals who participate in citizen science projects are demographically speaking not very diverse. For citizen science projects to successfully achieve their full potential in increasing public awareness and understanding of science, a wider social demographic needs to be engaged.We present a nationwide approach developed to achieve just that with respect to targeting and engaging residents in Denmark that did not previously have a prior connection to or interest in nature. Under the auspices of a campaign entitled Our Nature, our approach included the formation of a new, cross-sectoral partnership, and co-creating and implementing of a wide array of communication tactics and nature-based activities, including the development of a new citizen science project. Our cross-sectoral partnership allowed us to broaden the sectors of society that could be reached and develop cross-disciplinary activities to achieve goals for broad engagement. Extensive third-party evaluation revealed that 70 % of the Danes interviewed across the country heard about Our Nature, and 70 % of these gained more knowledge about Danish nature through the campaign. In addition to presenting our co-created projects and activities by working cross-sectorally and 2 interdisciplinarily, we discuss the successes, challenges and limitations related to reaching our goal, based on evaluation results and our own experiences in citizen science and science communication. The citizen science project Denmark Explores that emerged from this campaign is used as a case study to demonstrate how our approach facilitated the broad engagement of citizens across the country--beyond the usual nature enthusiasts.